Vocabulary size in very preterm and extremely preterm infants: a cross-sectional study - Varela-Moraga, Virginia; Arce-Montero, Constanza; Ramírez -Carreño, Fernanda; Osorio-Saldaña, Camila; Quezada-Gaponov, Camilo (Revista Chilena de Fonoaudiología, 2023)
Research shows that a significant number of children born preterm (before 37 weeks of gestation) have developmental difficulties, among them disturbances in language development. Studies indicate that some biomedical complications such as intraventricular hemorrhage (grades III and IV), periventricular leukomalacia, and bronchopulmonary dysplasia increase the probability of cognitive and/or language development disorders. Therefore, there is a need to conduct more studies that provide information that allows anticipating possible consequences in the learning process of children born prematurely. The aims of this study were to measure the early vocabulary size in very preterm and extremely preterm children (with and without biomedical complications) at 24 months of corrected age and to determine the association between the number of biomedical complications and vocabulary size. To that effect, we worked with 108 children divided into three groups: 39 high-risk preterm children (with biomedical complications), 36 low-risk preterm children (without biomedical complications associated with language and/or cognitive disturbances), and 33 full-term children. All children were evaluated using the MacArthur-Bates Communicative Development Inventory II. The results show that the vocabulary size of full-term children is significantly larger than that of preterm children and that no differences exist between the group of high-risk versus low-risk preterm children. On the other hand, vocabulary size does not correlate with biomedical complications.